Proposta de um modelo de serviço de reabilitação auditiva do municipio de São Paulo - Mouradian, Cláudia Aparecida Ragusa (2021)
The aim of this research was to present a case study of a hearing rehabilitation service in the city of São Paulo and an nalysis of its implementation. This model was constructed from the reorganization of the patient's auditory rehabilitation process, proposed by the Technical Area of People with Disabilities of the Municipal Health Department, introducing the Shared Multiprofessional Reception, with a view to that established in the Care Line and the Singular Therapeutic Project. Previously, patients in the region scheduled for diagnosis complied with the following Protocol: 1. ENT physician - Service Entry; 2. Audiological Evaluation; 3. Otorhinolaryngologist - diagnosis and conduct; 4. Speech therapist - pre-mold and pre-selection of the device; 5. Speech therapist - Test and definition of the Device and 6. Delivery /Dispensing of the Device, and such process of entry to the concession of hearing aids took up to 12 months. The reorganization took place in 4 Phases, from April/2015 to April/2017, allowing the scheduling to perform Steps 1, 2, 3 and 4 of the Protocol and inclusion of social work on the same day. With this operating model, it was observed a reduction in the number of returns, optimization of schedules, improvement of access to the service and reduction of the time between the first consultation and the granting of hearing devices from twelve to four months. The patient's process for auditory rehabilitation within the Service was all restructured and described, constituting a model to be replicated. In the 2nd Study, we analyzed the time markers between the stages proposed in this model and the patients' support the consultations scheduled in the adaptation of the hearing aids granted. The results can contribute as a management tool in the search for quality indicators